Relationship Between Knowledge and Hypertension History with Blood Pressure Control in Elderly - Destiara Hesriantica Zaenurrohmah; Riris Diana Rachmayanti (Jurnal Berkala Epidemiologi, 2017)
Hypertension is one of the main causes of mortality and morbidity in Indonesia, so the management of this disease is a very common intervention carried out at various levels of health facilities. The results of Indonesia's basic health research in 2013 most diseases in the elderly are hypertension, as many as 57.6% followed by arthritis (51.9%) and stroke (46.1%). Based on the results of blood pressure examinations at the Integrated health care post for the elderly (Posyandu Lansia) Melati, it is known that the majority of elderly people experience prehypertension. This study aims to analyze the relationship between the level of knowledge of the elderly about hypertension and the history of hypertension with control measures in the elderly in Posyandu Lansia Melati, Ampel Village, Semampir Sub-district, Surabaya City. This study was an observational study with cross-sectional study design. This research was conducted in March 2017 at Posyandu Lansia Melati. The population of this research is the elderly who make a visit to Posyandu Lansia Melati. The independent variables studied were knowledge and history of hypertension, while the dependent variable was blood pressure control measures. The total samples in this study were 50 elderly. Primary data collection was carried out using a questionnaire. Data analysis using the Chi-Square test. The results of the bivariate analysis showed a relationship between the history of hypertension and control measures (p = 0.019.  The conclusion in this study the history of hypertension has a relationship with control measures, so it is advisable to carry out communication, information, and education  about hypertension in the elderly in Posyandu through counseling or the presence of the media.